Fluorescence labelling of extracellular vesicles using a novel thiol-based strategy for quantitative analysis of cellular delivery and intracellular traffic. Issue 36 (7th September 2017) - Roberts-Dalton, H. D.; Cocks, A.; Falcon-Perez, J. M.; Sayers, E. J.; Webber, J. P.; Watson, P.; Clayton, A.; Jones, A. T.
Abstract : Prostate cancer EVs remain differentiation competent when fluorescently labelled using a novel thiol-based method, allowing exploration of their endocytosis and trafficking. Abstract : Extracellular vesicles, including exosomes, are naturally derived nanovesicles generated in and released by numerous cell types. As extracellular entities they have the capacity to interact with neighbouring cells and distant tissues and affect physiological processes as well as being implicated in numerous diseases including tumorigenesis and neurodegeneration. They are also under intense investigation as delivery vectors for biotherapeutics. The ways in which EVs interact with recipient cells to influence cell physiology and deliver a macromolecular payload are at the early stages of exploration. A significant challenge within these studies is the ability to label EVs directly or indirectly with fluorescent probes to allow visualization without compromising functionality. Here, we present a thiol-based fluorescence labelling method allowing comprehensive analysis of the cellular uptake of prostate cancer derived EVs in live cells using confocal microscopy. Labelling of the EVs in this way did not influence their size and had no effect on their ability to induce differentiation of lung fibroblasts to myofibroblasts. For endocytosis analyses, depletion of key endocytic proteins and the use of chemical inhibitors (Dynasore, EIPA, Rottlerin and IPA-3) indicated that fluid-phase endocytosis and/or macropinocytosis was involved in EV internalisation. Over a period of six hours EVs were observed to increasingly co-localise with lysosomes, indicating a possible termination point following internalisation. Overall this method provides new opportunities for analysing the cellular dynamics of EVs as biological entities affecting cell and whole body physiology as well as investigating their potential as drug delivery vectors.